Zgodovina raziskovanja luminiscentnih snovi - Južnič, Stanislav (Vakuumist, 1997)
Third part of article deals with radio- and cathodoluminiscence with special concern put on Brauns' tube. A concluding part of discussion in dedicated to luminiscence research in Austria and Slovenia lands.
Keywords: fizika; physics; luminiscenca; zgodovinski prikazi